The Process of Reforms Civil Code as New Openings Prospects to Access to Justice - Belchior Silva, Luiz De França (2017)
This work aims to analyze the access to justice from the perspective of the last Brazilian judicial reforms that attempt to compromise the slow pace of justice in the provision of judicial protection, as emerged reforms with the new Civil Procedure Code, in the reasonable duration of the process consolidated themselves as fundamental principle infra and other procedural mechanisms such as the electronic process, the procedural calendar, conciliation, and in alternative dispute resolution, such as mediation and arbitration, causing justice to be seen as a broader system, Multiport Court, presenting highly relevant in procedural legal scenario.